ANALYZING PRODUCT PLACEMENT EFFECTIVENESS IN KOREAN DRAMA THROUGH NETFLIX PLATFORM IN MANADO - Mumu, Elisabeth Margareth; Lapian, Joyce; Pandowo, Merinda (Universitas Sam Ratulangi, 2024)
The effectiveness of product placement in Korean dramas streamed on Netflix, specifically in the city of Manado. The study employs three key indicators to assess effectiveness: Visual, Auditory, and Plot Dimensions. The Visual Dimension examines how prominently and attractively products are featured within scenes. The Auditory Dimension evaluates the impact of verbal mentions or sounds associated with the product. Lastly, the Plot Dimension assesses how seamlessly the product integrates into the storyline and influences viewer perception. By analyzing these dimensions, the study aims to provide a comprehensive understanding of how product placement impacts viewer engagement and brand recall in this specific demographic. Keyword: Product Placement, Visual Dimension, Auditory Dimension, Plot Dimension